2014
DOI: 10.17509/ijal.v3i2.662
|View full text |Cite
|
Sign up to set email alerts
|

Let’s Talk and Tolerate: Strengthening Students Cultural Awareness Through Literature Circles

Abstract: Putting more attention on teaching language skills, the use of literature in EFL classrooms is often abandoned. While essentially, exploiting literary texts in some advanced EFL courses, serves a variety of purposes, dedicated to encourage interactive and communicative classes for language learners at different levels of proficiency. Literary texts often offer cultural explorations through the embedded cultural contexts in the stories. Indeed, exploring literary works provides an exercise in cultural relativit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Literature circles provide an opportunity for lowerachiever or introvert learners to participate actively (Azmi, 2013). Similarly, Moecharam and Sari (2014) find that literature circles encourage every single learner to talk actively and eliminated any unnoticed opinions.…”
Section: Equal Participationmentioning
confidence: 96%
See 1 more Smart Citation
“…Literature circles provide an opportunity for lowerachiever or introvert learners to participate actively (Azmi, 2013). Similarly, Moecharam and Sari (2014) find that literature circles encourage every single learner to talk actively and eliminated any unnoticed opinions.…”
Section: Equal Participationmentioning
confidence: 96%
“…Learners can gain genre knowledge from role sheets and role-based discussions (Widodo, 2016) and improve soft skills such as learner autonomy and teamwork skills (Azmi, 2013;Widodo, 2016). Additionally, they can develop cultural awareness (Moecharam & Sari, 2014) and writing creativity (Lubis, 2018). The learning atmosphere of literature circles advances literacy development (Coffey, 2012, p. 396) because the learners in-turn take on specific responsibilities, discuss reading content, and cooperatively share different perspectives (Widodo, 2016).…”
Section: Literature Circles In Efl Settingsmentioning
confidence: 99%
“…As a teacher, I strongly believe and identify my teaching creed with Erkaya's viewpoint "that literature can be used to reinforce language skills and complement teaching" (Erkaya, 2005, p.3). Cultural enrichment, which is in line with all language learning theories and the recommendations contained in the CEFR can be successfully attained through judiciously selected LT. Interacting with literature belonging to different geographical areas and historical periods not only contributes to expanding the students' knowledge of culture, but also plays a crucial role in opening their minds to change and diversity (Moecharam, 2014). Obviously, the advantages a literary piece of writing could bring into the language classroom outweigh by far its drawbacks and even if it means that there is an extra effort for the teacher, it is definitely worth it: short term, there might be a feeling of Sisyphean task, but long term, the outcomes will be absolutely rewarding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The utilization to strengthen students character or skill have been proven by several pieces of research. Moecharam and Kartikasari (2014) concluded that literary works can be utilized to develop students cultural awareness [10]. Anderson (2014) concluded that literary works can be used to cultivate students cultural competence [11].…”
Section: The Forms Of Inspiration Of Tolerance From the Short Storymentioning
confidence: 99%